Problems of Arabic Teaching for Students of The Government Islamic High School Semarang - Rokhani, Rokhani; Hamdi, Izdihar; Zainurrakhmah, Zainurrakhmah (Borneo Journal of Language and Education, 2022)
The Arabic language has four skills required by all non-native speaking students, especially students from the government school in Samarang, Indonesia. It is the skill of listening, speaking, reading and writing. All of these skills are necessary for non-native students to try to understand them. Although students learn it from a young age, they cannot master this language well. Rather, they face many problems, including difficulty understanding word structures and comprehension of new foreign vocabulary. This research aims to identify the problems of teaching Arabic to students of the Islamic High School in Samarang and solve their problems. This research was a field research using the qualitative approach in conjunction with the use of the current study as one of its methods. Data collection is carried out in three ways: observation, interview, and documentation. The method used to analyze research data is reduction, presentation and investigation. The result of the research was obtained that the problems faced by students of the public secondary school Smaring are of two types, namely the linguistic problem and the non-linguistic problem, and the linguistic problem is vocabulary and structures. The non-linguistic problem is the lack of motivation and enthusiasm of students and the lack of a learning environment. The solutions proposed by the researcher are 1) accustoming students to speech as much as they can, 2) using fun method and strategy such as language games and others, 3) fixing school decisions related to the motivation for their learning of the Arabic language, such as warning and excuse.